Impact of recapitalisation and dividend payout policies on financial sustainability of rural and community banks in Ghana - Richard Oduro (Future Business Journal)
Abstract The study examines the effect of bank recapitalization and dividend policies on the financial sustainability of rural and community banks (RCBs) in Ghana. Data from 135 RCBs from 2011 to 2020 revealed an average financial sustainability index of 0.525 over the past decade, suggesting that RCBs can finance their operations and liabilities without diminishing shareholder value. Recapitalization and dividend payouts positively impact financial sustainability, with well-capitalized, highly pay-out RCBs showing faster improvements in sustainability compared to those with retention policy. This highlights the importance of RCBs bolstering their capital base, even when not mandated by regulators, to enhance financial sustainability. Furthermore, adopting a relaxed pay-out policy can signal operational efficiency and sustainability to shareholders.